The structural dynamics of α-tropomyosin on F-actin shape the overlap complex between adjacent tropomyosin molecules - Lehman, William; Li, Xiaochuan (Edward); Orzechowski, Marek; Fischer, Stefan (Archives of biochemistry and biophysics, 2014)
Coiled-coil tropomyosin, localized on actin filaments in virtually all eukaryotic cells, serves as a gatekeeper regulating access of the motor protein myosin and other actin-binding proteins onto the thin filament surface. Tropomyosin’s modular pseudo-repeating pattern of approximately 39 amino acid residues is designed to allow binding of the coiled-coil to successive actin subunits along thin filaments. Even though different tropomyosin isoforms contain varying numbers of repeat modules, the pseudo-repeat length, in all cases, matches that of a single actin subunit. Thus, the seven pseudo-repeats of 42nm long muscle tropomyosin bind to seven successive actin subunits along thin filaments, while simultaneously bending into a super-helical conformation that is preshaped to the actin filament helix. In order to form a continuous cable on thin filaments that is free of gaps, adjacent tropomyosin molecules polymerize head-to-tail by means of a short (∼9 residue) overlap. Several laboratories have engineered peptides to mimic the N- and C-terminal tropomyosin association and to characterize the overlap structure. All overlapping domains examined show a compact N-terminal coiled-coil inserting into a partially opened C-terminal partner, where the opposing coiled-coils at the overlap junction face each other at up to ∼90° twist angles. Here, Molecular Dynamics (MD) simulations were carried out to determine constraints on the formation of the tropomyosin overlap complex and to assess the amount of twisting exhibited by full-length tropomyosin when bound to actin. With the exception of the last 20-40 C- and N-terminal residues, we find that the average tropomyosin structure closely resembles a “canonical” model proposed in the classic work of McLachlan and Stewart, displaying perfectly symmetrical supercoil geometry matching the F-actin helix with an integral number of coiled-coil turns, a coiled-coil helical pitch of 137Å, a superhelical pitch of 770Å, and no localized pseudo-rotation. Over the middle 70% of tropomyosin, the average twisting of the coiled-coil deviates only by 10° from the canonical model and the torsional freedom is very small (std. dev. of 7°). This small degree of twisting cannot yield the orthogonal N- and C-termini configuration observed experimentally. In marked contrast, considerable coiled-coil unfolding, splaying and twisting at N- and C-terminal ends is observed, providing the conformational plasticity needed for head-to-tail nexus formation.